THE DEVELOPMENT OF CHILDREN'S EMOTIONAL: A SYSTEMATIC LITERATURE REVIEW - Tri Wulandari (Universitas Pendidikan Indonesia, 2021)
One aspect of development that is important for early childhood is the emotional aspect. Summarizing the opinion of Goleman, Izard and Ackerman, Le Doux, (Hansen Zambo 2007) emotions are feelings that are physiologically and psychologically owned by children and are used to respond to events that occur around them. Emotions develop over time, emotions in early childhood develop from simple to more complex conditions. Emotions develop as a result of interaction with the environment. Emotional development in early childhood is very important. Because emotional behavior has to do with activities with activities in life. The stronger the emotion exerts pressure, the stronger it will shake the balance of the body to perform certain activities. And that is the reason for me to write this article using a systematic literature review method that examines journals according to the topics I discuss